2017
DOI: 10.1016/j.agee.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Management of pig manure to mitigate NO and yield-scaled N2O emissions in an irrigated Mediterranean crop

Abstract: Substitution of conventional mineral fertilizers with organic sources can avoid the environmental problems associated with high concentrations of intensive livestock production in some Mediterranean areas. Some management practices, such as the use of nitrification inhibitors or more efficient irrigation techniques (e.g., drip irrigation), have been suggested as effective alternatives to mitigate nitrous oxide (N 2 O) and nitric oxide (NO) emissions released from soils amended with synthetic and organic fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 49 publications
3
21
1
Order By: Relevance
“…This study showed that the use of DMPP could be considered an effective strategy to reduce direct N2O emissions from PS (reduction of c. 70% of N2O emissions) mainly because, as reported by Chadwick et al (2011), under the study conditions, an important fraction of N2O emitted after DMPP application was produced through nitrification. Our results also confirm those of Guardia et al (2017b) who observed a 49% inhibitory effect of DMPP on N2O emissions when 120 kg N ha -1 of liquid PS fraction was applied to a maize crop. Additionally, DMPSA mitigated 40% of total N2O fluxes within the first three weeks after top-dressing fertilizer application, with N2O losses in DMPSA plots similar to those of the unfertilized treatment (Table 5.2).…”
Section: Effect Of Nitrification Inhibitors On Nitrous Oxide Emissionssupporting
confidence: 91%
See 2 more Smart Citations
“…This study showed that the use of DMPP could be considered an effective strategy to reduce direct N2O emissions from PS (reduction of c. 70% of N2O emissions) mainly because, as reported by Chadwick et al (2011), under the study conditions, an important fraction of N2O emitted after DMPP application was produced through nitrification. Our results also confirm those of Guardia et al (2017b) who observed a 49% inhibitory effect of DMPP on N2O emissions when 120 kg N ha -1 of liquid PS fraction was applied to a maize crop. Additionally, DMPSA mitigated 40% of total N2O fluxes within the first three weeks after top-dressing fertilizer application, with N2O losses in DMPSA plots similar to those of the unfertilized treatment (Table 5.2).…”
Section: Effect Of Nitrification Inhibitors On Nitrous Oxide Emissionssupporting
confidence: 91%
“…Additionally, DMPSA mitigated 40% of total N2O fluxes within the first three weeks after top-dressing fertilizer application, with N2O losses in DMPSA plots similar to those of the unfertilized treatment (Table 5.2). Guardia et al (2017b) found a significant inhibitory effect of 57% when applying CAN and DMPSA (180 kg N ha -1 ), also in a maize crop in a clay soil, suggesting that nitrification was the dominant N2O production process at the peaking time. The nitrification inhibitory effect of DMPSA is not well known yet, but probably its effect is based on the presence of dimethylpyrazole (DMP), which is released through the degradation of succinic acid in soil.…”
Section: Effect Of Nitrification Inhibitors On Nitrous Oxide Emissionsmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, water supply can also increase N2O emissions favoring conditions for nitrification and denitrification (Maris et al, 2015), while a rational management of irrigation can enhance crop yield and mitigate the impact of cropping systems on environment and global climate by favoring Carbon sequestration and reducing GHGs emission. Most of the studies on the effects of NIs and organic and organomineral fertilisers on crop production and N2O emission has been carried out under optimal irrigation conditions (Vitale et al, 2013;Guardia et al, 2016;Huérfano et al, 2016;Vitale et al, 2017), while little information is available for open field crops under reduced water supply (Albalos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, several different approaches have been proposed in terms of appropriate management of irrigation (Vallejo et al, 2014;Meijjde et al, 2016;Wolff et al, 2016) as well as of fertilisation, such as the use of fertilisers added with nitrification inhibitors (NIs) (Vitale et al, 2013;Abalos et al, 2016;Hube et al, 2016;Huérfano et al, 2016;Vitale et al, 2017) and organo or organomineral fertilisers (Ball et al, 2004;Guardia et al, 2016;Vitale et al, 2017). The latter release nitrogen (N) more gradually over the course of season, compared to conventional mineral fertilisers, thus improving synchrony between soil N availability and crop N demand and potentially increasing overall efficiency of fertiliser use.…”
Section: Introductionmentioning
confidence: 99%